Correlates and determinants of direct democracy - Lorenz Blume; Bernd Hayo; Stefan Voigt (Philipps-University Marburg, Faculty of Business Administration and Economics, 2015)
This paper studies correlates and determinants of direct democracy institutions (DDIs), such as referendums and initiatives, based on the premise that constitutions themselves are endogenous. Our sample covers as many as 132 countries from 1950 to 2006. We find that the likelihood that a country includes DDIs in its constitution increases over time, particularly during the 1990s and 2000s. In our econometric analysis, we employ a two-tier approach, the first tier analyzing the time-invariant factors associated with the existence of DDIs, the second tier focusing on changes in time-variant factors. We discover that (i) new constitutions make the introduction of DDIs more likely; (ii) the degree of democratization is positively related to constitutions containing DDIs; (iii) an increase in the number of riots and assassinations raises the likelihood of constitutionally anchoring DDIs; (iv) if political leaders achieved power or were removed from office through irregular means, the introduction of DDIs is more likely; if they leave office due to health reasons, DDIs are less likely to be included in the constitution; and (v) religious fractionalization is negatively associated with the possibility of referendums.
Keywords: D72; H11; P51; 330; Direct Democracy; Referendums; Initiatives; Endogenous Constitutions